Construction and validation of Iranian EFL teachers’ teaching motivation scale - Goudarz Alibakhshi; Behzad Nezakatgoo (Cogent Education, 2019)
During the last few decades, motivation to learn English has become an interesting research area. However, the studies on EFL teachers’ motivations for choosing teaching as their career, to the present date, are scanty. The present study was an attempt to construct and validate a teaching motivation scale for EFL teachers. In the qualitative results phase, the main motivations for selecting teaching were extracted and categorized into motivational types: intrinsic and extrinsic. Results of quantitative phase showed that the developed method enjoyed an acceptable construct validity. The findings can be used by teacher trainers and organizations involved in recruiting EFL teachers.